2021
DOI: 10.1039/d1cp00985k
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-free dynamic nuclear polarization enhancements in organically modified mesoporous silica

Abstract: High-field Dynamic Nuclear Polarization is a powerful tool for the structural characterization of species on the surface of porous materials or nanoparticles. For these studies the main source of polarization...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Furthermore, Tsutsui et al demonstrated that the surface of Au micropores was modified with a synthetic peptide designed from toll-like receptor 5 (TLR5), which exhibited intermolecular interactions with Escherichia coli . Brodrecht et al have recently conducted direct solid-phase peptide synthesis (SPPS) inside the silica mesoporous nanoparticles. They exhibited the capacity to monitor chemical changes occurring on the pore surface and modifications in the material’s pore properties throughout each of the successive functionalization steps. Moreover, they achieved the synthesis of the desired peptide sequence by employing a sequential coupling process for each amino acid.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Tsutsui et al demonstrated that the surface of Au micropores was modified with a synthetic peptide designed from toll-like receptor 5 (TLR5), which exhibited intermolecular interactions with Escherichia coli . Brodrecht et al have recently conducted direct solid-phase peptide synthesis (SPPS) inside the silica mesoporous nanoparticles. They exhibited the capacity to monitor chemical changes occurring on the pore surface and modifications in the material’s pore properties throughout each of the successive functionalization steps. Moreover, they achieved the synthesis of the desired peptide sequence by employing a sequential coupling process for each amino acid.…”
Section: Introductionmentioning
confidence: 99%
“…26−28 Specifically, amine groups are suitable to form covalent amide bonds by reaction with carboxyl moieties that enable them to bind amino acids or peptides. 29 Two complementary approaches are known to incorporate APTES linker groups into silica materials: (i) the linker molecule can be attached to the silanol groups in the pores of the material via covalent binding after the mesoporous material is synthesized (grafting approach), or (ii) the linker molecule can be tethered during the synthesis of the material (co-condensation approach). 30 The interest in studying the dynamics of molecules in confinement has increased significantly in the past few years.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Three-aminopropyl triethoxysilane (APTES) is one of the most widely used functionalization agents to modify silica surfaces since the presence of the terminal amine group (–NH 2 ) allows attaching or “linking” moieties of interest such as drugs, biomolecules (enzymes, DNA, proteins, etc. ), and homogeneous transition metal catalysts. Specifically, amine groups are suitable to form covalent amide bonds by reaction with carboxyl moieties that enable them to bind amino acids or peptides . Two complementary approaches are known to incorporate APTES linker groups into silica materials: (i) the linker molecule can be attached to the silanol groups in the pores of the material via covalent binding after the mesoporous material is synthesized (grafting approach), or (ii) the linker molecule can be tethered during the synthesis of the material (co-condensation approach) …”
Section: Introductionmentioning
confidence: 99%
“…19 However, these studies did not employ spherical and monodispersed SiO 2 NPs, and the samples could only be partially polarized. 20 Herein, we developed radical-embedded SiO 2 NPs in which modified 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) acted as an internal electron-spin source for hyperpolarization during DNP. In particular, we synthesized radical-embedded SiO 2 NPs using tetraethyl orthosilicate (TEOS) and 1-[3-(triethoxysilyl)propyl]-3-[4-(2,2,6,6-tetramethylpiperidine-1oxyl)]urea (TEOS-TEMPO) through the Stöber method and ORMOSIL NP approach (Scheme 1).…”
mentioning
confidence: 99%
“…This may have resulted in the paramagnetic quenching of the DNP signal, consequently resulting in low intensities. 20,21 Based on the build-up curves, the build-up time constants of all samples were determined using a monoexponential function. Considering the fitted data, the CORE SiO 2 NP samples displayed the fastest build-up time constant (16 min) compared to that of NORMAL (83 min), SHELL (36 min), and HOMO (22 min) samples.…”
mentioning
confidence: 99%